Attention in Active Vision: A Perspective on Perceptual Continuity Across Saccades. (August 2015) - Rolfs, Martin
Alfred L. Yarbus was among the first to demonstrate that eye movements actively serve our perceptual and cognitive goals, a crucial recognition that is at the heart of today's research on active vision. He realized that not the changes in fixation stick in memory but the changes in shifts of attention. Indeed, oculomotor control is tightly coupled to functions as fundamental as attention and memory. This tight relationship offers an intriguing perspective on transsaccadic perceptual continuity, which we experience despite the fact that saccades cause rapid shifts of the image across the retina. Here, I elaborate this perspective based on a series of psychophysical findings. First, saccade preparation shapes the visual system's priorities; it enhances visual performance and perceived stimulus intensity at the targets of the eye movement. Second, before saccades, the deployment of visual attention is updated, predictively facilitating perception at those retinal locations that will be relevant once the eyes land. Third, saccadic eye movements strongly affect the contents of visual memory, highlighting their crucial role for which parts of a scene we remember or forget. Together, these results provide insights on how attentional processes enable the visual system to cope with the retinal consequences of saccades.